2020
DOI: 10.3233/bd-190435
|View full text |Cite
|
Sign up to set email alerts
|

An audit of over 1000 breast cancer patients from a tertiary care center of Northern India

Abstract: Background: Breast cancer is the commonest cancer among women. India along with United States and China collectively account for one third of the global burden. The present study reports the clinico-epidemiological data of our patient population. This may help in better understanding of the disease in our population and also form ground for conducting further breast cancer research in India. Methods: The study was conducted at an apex teaching and medical research institution in India from September 2013 to Ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 30 publications
2
11
0
Order By: Relevance
“…According to Neelam Sharma's findings, 75% of the respondents had a low socioeconomic status study findings corresponds to present study [16]. According to Suhani S. et al (2020), 50 % of post -menopausal women 39 (32.5%) of those who participated were over the age of 45 current findings corresponds with the study [17].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…According to Neelam Sharma's findings, 75% of the respondents had a low socioeconomic status study findings corresponds to present study [16]. According to Suhani S. et al (2020), 50 % of post -menopausal women 39 (32.5%) of those who participated were over the age of 45 current findings corresponds with the study [17].…”
Section: Discussionsupporting
confidence: 86%
“…Present study found 81.66% women were married findings were congruent with Nitin Gangane et al A 2017 study the majority of participants, or 83.6%, were married [15]. Current study found that 90% of participants had no family history of breast cancer, similar findings were reported by Suhani S. et al (2020)15% of the participants had a family history of BC [17]. B et al 2016 reported that approximately 89 percent of participants had mastectomy and surgical treatment, which corresponds with the current study [18].…”
Section: Fig 1 Categories Of Levels Of Unmet Needs For Breast Cancer ...supporting
confidence: 88%
“…Of course, there are some populations with higher rates of breast cancer in men. For example, the male breast rate is 1.1% in Northern India [ 75 ], and it is higher in some populations in Africa (6.2% in North Uganda [ 76 ], 2.6% in Burkina Faso [ 77 ], and 3.2% in 27 African countries [ 78 ]). Epidemiological differences between different groups of people may be related to region, race and living environment.…”
Section: Discussionmentioning
confidence: 99%
“…The median incidence of invasive lobular carcinoma is about 11% in Western countries [40]. These tumors are predominantly ER-and PRpositive and Her2-negative [41][42][43][44][45][46] and the majority of Her2positive lobular carcinomas are pleomorphic variants [44,45]. We report a 12.7% rate of lobular carcinomas.…”
Section: Dcismentioning
confidence: 73%